Mechanical Chest Compressions in Prolonged Cardiac Arrest due to ST Elevation Myocardial Infarction Can Cause Myocardial Contusion - Stechovsky, Cyril; Hajek, Petr; Cipro, Simon; Veselka, Josef (The International journal of angiology, 2016)
Acute coronary syndrome is a common cause of sudden cardiac death. We present a case report of a 60-year-old man without a history of coronary artery disease who presented with ST-elevation myocardial infarction. During transportation to the hospital, he developed ventricular fibrillation (VF) and later pulseless electrical activity. Chest compressions with LUCAS 2 (Medtronic, Minneapolis, MN) automated mechanical compression-decompression device were initiated. Coronary angiography showed total occlusion of the left main coronary artery and primary percutaneous coronary intervention (PCI) was performed. After the PCI, his heart started to generate effective contractions and LUCAS could be discontinued. Return of spontaneous circulation was achieved after 90 minutes of cardiac arrest. The patient died of cardiogenic shock 11 hours later. An autopsy revealed a transmural anterolateral myocardial infarction but also massive subepicardial hemorrhage and interstitial edema and hemorrhages on histologic samples from regions of the myocardium outside the infarction itself and also from the right ventricle. These lesions were concluded to be a myocardial contusion. The true incidence of myocardial contusion as a consequence of mechanical chest compressions is not known. We speculate that severe myocardial contusion might have influenced outcome of our patient.
Keywords: cardiac arrest; percutaneous coronary intervention; mechanical chest compressions; myocardial contusion; ST-elevation myocardial infarction